Impaired learning and memory in Pitx3 deficient aphakia mice: A genetic model for striatum-dependent cognitive symptoms in Parkinson's disease - Ardayfio, Paul; Moon, JiSook; Leung, Ka Ka Amanda; Youn-Hwang, Dong; Kim, Kwang-Soo (Neurobiology of disease, 2008)
Disorders of the basal ganglia such as Parkinson's disease (PD) and Huntington's disease are commonly thought of primarily as motor disorders; however, the cognitive symptoms of these diseases such as executive dysfunction, learning, memory and attention deficits are prominent and often more disabling than the hallmark motor symptoms. Cognitive features of PD are often neglected in preclinical studies of PD, likely due to the lack of available animal models to study them. Aphakia mice, which are deficient in the transcription factor Pitx3, model the selective nigrostriatal DA loss in PD. Here we report that aphakia mice are impaired in striatum-dependent cognitive tasks including rotarod learning, T-maze and inhibitory avoidance tasks, but not the striatum-independent social transmission of food preference task. These results suggest that some neuropsychiatric symptoms in PD are related to the pathophysiology of the disease rather than stress associated with disease burden, or medications used to treat PD. Furthermore aphakia mice may be used as a novel model of non-motor symptoms in PD.